Resistance exercise training improves disuse-induced skeletal muscle atrophy in humans: a meta-analysis of randomized controlled trials - Xian Guo; Yanbing Zhou; Xinxin Li; Jinhao Mu (BMC Musculoskeletal Disorders)
Abstract Background This meta-analysis aimed to determine whether resistance exercise training (RET) can attenuate the loss of muscle volume and function in anti-gravitational muscles, especially quadriceps and calf muscles, during immobilization/disuse conditions. Methods A comprehensive literature search was conducted to identify randomized controlled trials comparing RET vs. no exercise during immobilization/disuse. Searches were conducted in databases including Web of Science, PubMed, EBOSCO, and Cochrane Library, without imposing a time limit until 20 March, 2023. Studies reporting outcomes related to muscle volume, MVC, peak power, concentric peak force, eccentric peak force, isometric MVC torque of knee extension, isometric MVC torque of knee flexion were included. Data were pooled using random-effects models. Results Eleven randomized controlled trials were finally included. RET elicited substantial benefits for preserving quadriceps muscle volume (n = 5, MD = 252.56, 95% CI = 151.92, 353.21, p < 0.001). RET demonstrated a statistically significant preventive effect on the reduction of MVC in both quadriceps (n = 4, MD = 338.59, 95% CI = 247.49, 429.69, p < 0.001) and calf muscles (n = 3, MD = 478.59, 95% CI = 160.42, 796.77, p < 0.01). Peak power of quadriceps muscles (n = 4, MD = 166.08, 95% CI = 28.44, 303.73, p < 0.05) and calf muscles (n = 2, MD = 176.58, 95% CI = 102.36, 250.79, p < 0.001) were elevated after RET intervention. RET significantly ameliorated the weakening of both concentric and eccentric peak force in quadriceps (concentric: n = 2, MD = 470.95, 95% CI = 355.45, 586.44, p < 0.001; eccentric: n = 1, MD = 351.51, 95% CI = 254.43, 448.58, p < 0.001) and calf muscles (concentric: n = 2, MD = 867.52, 95% CI = 548.18, 1186.86, p < 0.001; eccentric: n = 1, MD = 899.86, 95% CI = 558.17, 1241.55, p < 0.001). Additionally, the diminishing of isometric MVC torques of knee extension (n = 6, MD = 41.85, 95% CI = 20.93, 62.77, p < 0.001) and knee flexion (n = 4, MD = 13.20, 95% CI = 8.12, 18.77, p < 0.001) were enhanced significantly after RET intervention. Conclusions RET effectively minimized deterioration of muscle volume and muscle function during immobilization/disuse, particularly in anti-gravitational muscles. RET should be recommended to maintain muscle and neuromuscular health for spaceflight, bed rest, immobilization/disuse conditions. Further research is needed to explore the effects of RET in more diverse populations and under various disuse conditions. More high-quality research will be required to demonstrate the aforementioned benefits conclusively.